World trade center- a true story of courage and survival - Cage, Nicolas; Gyllenhaal, Maggie; Bello, Maria; Pena, Michael ([United States] : Paramount Home Entertainment, 2006)
The unforgettable true story of the courageous rescue and survival of two Port Authority policemen who were trapped in the rubble on September 11, 2001, after they volunteered to go in and help the victims.
"Two thumbs up!"--Roeper & Kevin Smith.
"A powerful movie experience..."--Time Magazine.
"...genuinely stirring..."--New York Times.
"An expertly crafted, respectful piece of inspirational filmmaking."--New York Post.
Director, Oliver Stone.
Maggie Gyllenhaal, Maria Bello, Michael Pena, Nicolas Cage.
DVD.